When the Invisible Makes Inequity Visible: Chilean Teacher Education in COVID-19 Times - María Beatriz Fernández; Ilich Silva-Peña; Loreto Fernández; Catalina Cuenca (MDPI AG, 2022)
Although there is high inequity in the Chilean education system, the sanitary situation as a result of the COVID-19 pandemic has repositioned the debate about inequity in teacher education. We explored the following two questions: what are the (new) inequities highlighted in teacher education during the pandemic in Chile? What can we learn from teacher educators' responses to these issues? Using content analysis, we analyzed interviews held with 16 teacher educators from four different programs across the country. Findings show that the pandemic makes unequal pre-service teachers' living and studying conditions visible, becoming a source of stress but also an opportunity to rethink program support. Teacher educators' responses to inequity were based on a distributive and/or recognition perspective of justice, mediated by program resources and characteristics. We identified difficulties in achieving justice of participation by teacher educators in this context, influenced by scarce program resources or a sense of urgency. Conclusions highlighted the role of teacher education in addressing students' inequities and the importance of remaining vigilant about these issues in the aftermath of the pandemic, keeping them visible.